PENGARUH PAJAK, PROFITABILITAS, LEVERAGE, UKURAN PERUSAHAAN DAN MEKANISME BONUS TERHADAP TRANSFER PRICING - Ria Pamela (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2020)
Transfer pricing is a scheme to minimize the tax expense by transferring companies profit to another companies that located in countries with lower tax rate. This research aimed to examine the effect of tax, profitability, firm size and bonus mechanism on transfer pricing. The type of research used explanatory with quantitative approach. The sample consist of 27 multinational companies listed on Indonesia Stock Exchange in year 2014-2018 used purposive sampling technique. The analysis technique on this research used logistic regression analysis with E-Views 10 program. The result of this research showed that tax, profitability and firm size have significantly effect on transfer pricing. While leverage and bonus mechanism have no significantly effect on transfer pricing. The value of McFadden R-squared (R2) is 0.50 showed the relation among variables on this research is in medium category.